Penerapan Algoritma Fibonacci Code Pada File Transfer Berbasis Android - Dita Anggraini (Journal of Informatics Management and Information Technology, 2021)
Compression is to reduce a data size so that there is less memory to present than the original digital data presentation. For File Transfer Applications do not limit file types.Large data size results in memory wastage and delays in the process of transferring or punduplication of data so it needs to be done a way to minimize data storage.The size of files sent such as images, audio, video and documents. If the file transferred size is large enough then the file needs to be compressed so that the file size decreases and the ratio is 48%. The method applied to compress the file transfer application using the Fibonacci code algorithm